TUGAS DAN TANGGUNG JAWAB STAFF FRONT OFFICE PADA RUMAH SAKIT MEKARSARI - Damdam Damiyana; Dina Meiliana Sari (POLITEKNIK LP3I JAKARTA, 2020)
This research was conducted to find out how the responsibility of the Hospital front office staff in serving prospective patients. The study was conducted descriptively by direct observation and a brief interview with the front office supervisor. The writing of this report is presented descriptively to obtain an overview of various information relating to the provision of services to hospital customers. Methods of data collection using documentation studies, field studies and literature studies. The data obtained is then analyzed and presented descriptively. The conclusion can be drawn that the Mekarsari Hospital's Front Office has not been able to provide the best services for patients and their families, and in the Duties and Responsibilities of Front Office Staff must be able to create services that are Quick Response to problems, effective, efficient and prioritize patient safety.Keywords: Front Office, Hospital, Customers